Erratum to: 36th International Symposium on Intensive Care and Emergency Medicine: Brussels, Belgium. 15-18 March 2016 - Author et al; Bateman, R. M.; Sharpe, M. D.; Jagger, J. E.; Ellis, C. G.; Solé-Violán, J.; López-Rodríguez, M.; Herrera-Ramos, E.; Ruíz-Hernández, J.; Borderías, L.; Horcajada, J.; González-Quevedo, N.; et al. (Critical care (London, England), 2016)
[This corrects the article DOI: 10.1186/s13054-016-1208-6.].